2010
DOI: 10.1208/s12249-010-9465-1
|View full text |Cite
|
Sign up to set email alerts
|

The Transdermal Patches for Site-Specific Delivery of Letrozole: A New Option for Breast Cancer Therapy

Abstract: Abstract. The aim of this work was to evaluate capability of site-specific delivery of a transdermal patch through determination of letrozole in local tissues disposition in female mice. After transdermal administration, the letrozole levels in skin, muscle, and plasma were 10.4-49.3 μg/g, 1.64-6.89 μg/g, and 0.35-1.64 μg/mL, respectively. However, after the mice received letrozole suspension, the drug concentration of plasma and muscle were 0.20-4.80 μg/mL and 0.15-2.38 μg/g. There was even no drug determined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 11 publications
0
14
0
1
Order By: Relevance
“…This low inhibition is probably due to high drug lipophilicity, a reason for low bioavailability of oral posaconazole, and enhancement of drug bioavailability to up to 47% by high-fat food (Lipp, 2010). Drug lipophilicity and low apparent K d values for CYP27A1 (Table 1) make, however, ravuconazole and especially posaconazole, an approved Food and Drug Administration drug, good candidates for breast-specific drug delivery via transdermal patches, a route of administration that is currently under investigation (Li et al, 2010;Xi et al, 2010). Alternatively, posaconazole could be administered orally in combination with other antibreast cancer medications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This low inhibition is probably due to high drug lipophilicity, a reason for low bioavailability of oral posaconazole, and enhancement of drug bioavailability to up to 47% by high-fat food (Lipp, 2010). Drug lipophilicity and low apparent K d values for CYP27A1 (Table 1) make, however, ravuconazole and especially posaconazole, an approved Food and Drug Administration drug, good candidates for breast-specific drug delivery via transdermal patches, a route of administration that is currently under investigation (Li et al, 2010;Xi et al, 2010). Alternatively, posaconazole could be administered orally in combination with other antibreast cancer medications.…”
Section: Discussionmentioning
confidence: 99%
“…The mammary gland is a particularly suitable organ for tissue-specific drug delivery with efforts currently underway to administer some of the anticancer medication through the skin via transdermal patches (Li et al, 2010;Xi et al, 2010). This advantage of the mammary gland and body's tolerability to a partial lack of CYP27A1 activity supports enzyme potential as a pharmacologic target.…”
Section: Introductionmentioning
confidence: 99%
“…73 Although the present investigation appears to represent the first MTS study to use mice, previous preclinical studies have shown that shaved mice serve to model transdermal drug delivery. 74 Hairless or nude mice are more typically used for transdermal delivery studies across the range of patch technologies 75 ; however, the neuropharmacological reference strain status of the C57 mouse provided the justification for its use in investigating dl-MPH-ethanol interactions (see Introduction section). Maintaining the mice in the metabolic chambers for a total of 3 h allowed for the collection of adequate urine volume for analysis, while still permitting quantification of analytes from blood and brain.…”
Section: Discussionmentioning
confidence: 99%
“…Although the present investigation appears to represent the first MTS study to use mice, previous preclinical studies have shown that shaved mice serve to model transdermal drug delivery 74. Hairless or nude mice are more typically used for transdermal delivery studies across the range of patch technologies75; however, the neuropharmacological reference strain status of the C57 mouse provided the justification for its use in investigating dl‐ MPH–ethanol interactions (see Introduction section).…”
Section: Discussionmentioning
confidence: 99%